2003
DOI: 10.1007/s00122-003-1439-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of eggplant (Solanum melongena)-related germplasm: morphological and AFLP data contribute to phylogenetic interpretations and germplasm utilization

Abstract: A total of 94 Solanum accessions, including eggplants and related species, were morphologically characterized based on greenhouse observations, and molecularly analysed by the AFLP technique. Morphological parameters were helpful in assessing similarities or differences among accessions, and molecular data were used to support morphological conclusions. A dendrogram was computed based on the Dice genetic distances using the neighbour-joining method. The analysis was efficient in the assignment of a species nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
65
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 36 publications
7
65
0
3
Order By: Relevance
“…Occurrence of S. incanum together with S. melongena still in cluster IV also indicates relatedness and probably progenitors from a common ancestral lineage. This observation of closeness between S. incanum and S. melongena supports the earlier finding of Sakata and Lester (1994) that used chloroplast DNA, , Furini and Wunder (2004) and Singh et al (2006). In fact, had earlier observed that wild forms of S. incanum are regarded as belonging to the same species as S. melongena.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Occurrence of S. incanum together with S. melongena still in cluster IV also indicates relatedness and probably progenitors from a common ancestral lineage. This observation of closeness between S. incanum and S. melongena supports the earlier finding of Sakata and Lester (1994) that used chloroplast DNA, , Furini and Wunder (2004) and Singh et al (2006). In fact, had earlier observed that wild forms of S. incanum are regarded as belonging to the same species as S. melongena.…”
Section: Discussionsupporting
confidence: 89%
“…Furini and Wunder (2004), Singh et al (2006) and Levin et al (2006). However, these are not in agreement with some earlier workers; for instance, studied variation among the cultivated and weedy taxa of S. melongena by allozymes and RAPD analyses; also Ge et al (2013) examined the genetic diversity and relationships among eggplant accessions collected from seven areas in China using SSR markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is particularly useful for characterizing individual accessions and cultivars and as a general guide in the selection of the parents for hybridization (Furini and Wunder, 2004). Better knowledge on genetic diversity or genetic similarity could help to sustain long term selection gain (Chowdhury et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The AFLP technique (Vos et al 1995) generally produces between 50 and 100 scorable fragments per polimerase chain reaction (PCR) reaction (Maughan et al 1996). This technique has been widely used in various crops, including cultivated potatoes (Powell et al 1996;Milbourne et al 1997;McGregor et al 2000;Avrova et al 2002;Straadt and Rasmussen, 2003;Furini and Wunder, 2004) and their wild relatives (Kardolus et al 1998). In the last years, the AFLP technology was used to differentiate genotypes used as ancestors in potato genetic improvement programs.…”
mentioning
confidence: 99%